The manipulative mode : political propaganda in antiquity : a collection of case studies - Enenkel, K. A. E.; Pfeijffer, Ilja Leonard, 1968- (Mnemosyne, Supplements, 2005)
This book deals with political propoganda in classical antiquity, exploring the contexts, strategies, and parameters of a fascinating phenomenon that has often been approached with anachronistic models (such as the centrally organized 'propaganda machines' of the 20th-century totalitarian regimes) or completely ignored. It offers case studies on the archaic period, classical Athens, the Hellenistic kingdoms, the Augustan age and the late Roman empire, and emphasizes concepts such as interaction, integration, and horizontal orientation.